A method for preparing a magnesium-carbon refractory material resistant to attack by acid slags
Patent Information
- Application Number
- CN202611086799.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]本发明的目的在于针对各种工业窑炉中酸性熔渣极易化学溶解、渗透并破坏镁碳耐火材料中方镁石骨料的问题,提供一种氧化铬固溶改性镁砂骨料增强抗酸性渣侵蚀的镁碳耐火材料的制备方法
重构骨料表面物相,切断酸碱反应源头:传统镁碳砖骨料表面是裸露的高活性纯MgO晶体,极易溶于酸性熔渣。现有技术常通过引入Cr2O3、ZrO2粉体等提升材料抗侵蚀性能,而上述粉体孤立弥散或分布在基质中而缺乏与MgO组分之间的固溶结合,与酸性渣接触后MgO组分仍会发生溶蚀,使上述抗侵蚀组分并非起到真正抗侵蚀作用。Cr2O3是一种两性偏酸性氧化物,在高温预烧结时,Cr3+离子进入MgO晶格,取代了部分Mg²+离子形成固溶体。这种离子置换使得镁砂表面的整体碱性大幅减弱。对于酸性渣而言,固溶了Cr2O3的镁砂表面对酸性渣的惰性显著增强,从根本上降低了渣向骨料内部溶解的化学驱动力。
Smart Images

Figure CN122916620A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of refractory materials technology, and in particular to a method for preparing magnesia-carbon refractory materials resistant to acid slag erosion. Specifically, it relates to a method for improving the material's resistance to acid slag erosion by adjusting the surface solid solubility of magnesia aggregate with Cr2O3 and introducing it into the magnesia-carbon refractory material. Background Technology
[0002] In industrial processes such as non-ferrous metal smelting (e.g., copper, nickel, lead, and zinc smelting), special steel refining, and high-temperature molten reduction of complex associated minerals, refractory furnace linings frequently face harsh service environments characterized by high temperatures, variable atmospheres, and strongly acidic slag. Industrially, slag with a basicity (CaO / SiO2 mass ratio) less than 1.0 is generally defined as acidic slag. This type of acidic slag typically has low viscosity and high fluidity at high temperatures and contains a large amount of acidic oxides (such as SiO2, or accompanied by TiO2, V2O5, etc.). Currently, magnesia-carbon refractories are commonly used for the working linings of critical parts of these furnaces. Although magnesia-carbon refractories possess high refractoriness, good thermal shock resistance, and resistance to carbon oxidation, their aggregates, fused magnesia or sintered magnesia, face severe erosion by the acidic slag in acidic slag environments, thus affecting the smooth operation of key metal smelting. Because MgO is a strongly basic oxide, it has an extremely high chemical affinity for acidic slag and readily dissolves in the slag at high temperatures. Meanwhile, low-viscosity acidic slag rapidly penetrates into the magnesia aggregate along the pores and grain boundaries of the refractory material, undergoing a strong interfacial chemical reaction with the aggregate. This disrupts the crystal structure of periclase, leading to aggregate degradation, pulverization, and abnormal spalling, severely limiting the service life of the refractory lining. In existing technologies, to improve the resistance of refractory materials to acidic slag erosion, certain anti-erosion micropowders or additives are typically introduced directly into the fine powder of the magnesia-carbon brick matrix. However, this method of directly mixing and adding these additives into the matrix has the following drawbacks: First, it cannot counteract the penetrating chemical dissolution of the periclase aggregate itself by acidic slag; second, harmful or expensive micropowders such as free-state chromium salts, when directly heated in the matrix, often experience uneven local in-situ reactions, causing unstable volume expansion and resulting in a loose microstructure, which in turn accelerates the physical penetration of the slag. Therefore, composite refractory materials that spontaneously construct an acid-resistant slag barrier by modifying the microstructure of magnesia aggregate based on surface solid solubility control have important theoretical significance and engineering application value. Summary of the Invention
[0003] The purpose of this invention is to address the problem that acidic slag in various industrial kilns easily dissolves, penetrates, and damages the magnesia aggregate in magnesia-carbon refractories. This invention provides a method for preparing magnesia-carbon refractories with chromium oxide solution-modified magnesia aggregate to enhance resistance to acidic slag erosion. The invention employs a technical approach of first pre-sintering and surface solution modification, followed by mixing and brick making: before brick making, magnesia aggregate is embedded in Cr2O3 micro-powder and pre-sintered at high temperature to control the Cr content. 3+ The solid solubility of periclase in its surface lattice allows it to spontaneously react and form a continuous and dense protective layer of MgCr2O4 on the aggregate surface. Due to the extremely high melting point and natural high-temperature chemical inertness of MgCr2O4 against strongly acidic slags, the surface activity of the modified aggregate is significantly reduced. During service, this protective layer effectively prevents acidic slags (high-SiO2 slag, titanium / vanadium-containing acidic slag, etc.) from dissolving and penetrating into the aggregate, thus achieving a significant leap in the acid slag resistance of magnesia-carbon refractories.
[0004] A method for preparing a magnesia-carbon refractory material resistant to acid slag erosion, characterized by comprising the following steps: (1) Preparation of chromium oxide solution modified magnesia aggregate: By mass fraction, 70-85 parts of magnesia particles of 5-0.1 mm and 15-30 parts of Cr2O3 micro powder are mixed and a temporary binder is introduced. After molding, the mixture is pre-sintered at a high temperature of 1550℃-1650℃ for 3-5 hours to allow chromium oxide and periclase to react and dissolve on the surface of the particles and form a magnesia-chromium spinel layer. After cooling, crushing and grading, the chromium oxide solution modified magnesia aggregate of each particle size is collected. (2) Ingredients: The raw material composition and mass ratio of the refractory material are as follows: 50-62 parts of chromium oxide solution modified magnesia aggregate, 10-20 parts of SiC particles, 5-10 parts of pure magnesia fine powder, 1-3 parts of SiC fine powder, 2-4 parts of flake graphite fine powder, 1-3 parts of α-Al2O3 micro powder, 0.5-1.5 parts of pitch powder, 2-4 parts of metallic Si powder, 1-1.5 parts of B4C powder, and 3-4 parts of added liquid phenolic resin; (3) Mixing and molding: First, mix the solution-modified magnesium sand aggregate and SiC particles, then add phenolic resin to wet the surface of the aggregate, and finally add the matrix mixture powder premixed with the remaining powders. After mixing evenly, press the mixture under a pressure of 100-150 MPa. (4) Heat treatment: The molded body is dried at 180℃~220℃ for 24 hours to obtain a magnesium-carbon refractory material with enhanced resistance to acid slag erosion.
[0005] Further, the average particle size D of the Cr2O3 micro powder described in step (1) 50The particle size is 1-5 μm and its purity is > 99.0 wt%; the temporary binder is an aqueous solution of polyvinyl alcohol or an aqueous solution of sodium carboxymethyl cellulose, and the amount of temporary binder added is 2-4% of the total amount of magnesium sand particles and Cr2O3 micro powder.
[0006] Further, in the chromium oxide solution-modified magnesia aggregate described in step (2), 35-45 parts are 5-3 mm aggregate, 30-35 parts are 3-1 mm aggregate, and 20-30 parts are 1-0.1 mm aggregate; in the SiC particles, 20-40 parts are 3-1 mm SiC particles and 60-80 parts are 1-0.1 mm SiC particles.
[0007] Further, in step (3), the modified aggregate and SiC particles are premixed in a mixer for 3 to 5 minutes, phenolic resin is added and the mixture is continued to be mixed for 4 to 7 minutes, and finally the matrix mixing powder is added and the mixture is continued to be mixed for 10 to 15 minutes until the material is uniform.
[0008] Furthermore, after heat treatment at 200℃ for 24 hours, the resulting refractory material has a bulk density of 3.05–3.35 g / cm³. 3 The apparent porosity is 5.5%–7.5%, and the compressive strength at room temperature is 58–72 MPa. Under high-temperature acidic slag erosion conditions, the magnesia-chromium spinel layer on the surface of the modified magnesia aggregate has a chemical passivation effect, which can prevent the slag from chemically dissolving and chemically penetrating the magnesia aggregate.
[0009] In the slag erosion resistance test of typical non-ferrous / steelmaking acidic slag (basicity CaO / SiO2=0.4~0.7) held at 1600℃ for 0.5 hours, the material of this invention forms or retains a dense magnesium-chromium-magnesium-aluminum composite spinel barrier layer in situ at the interface between the slag and the aggregate, reducing the erosion chemical dissolution rate of magnesia inside the aggregate sample by more than 80%; when the material is subjected to an oxidation resistance test in an air atmosphere held at 1000℃ for 3 hours, the mass loss is only 1.2%~2.5%.
[0010] The significant advantages of this invention compared to existing technologies are: Reconstructing the aggregate surface phases to cut off the source of acid-base reactions: The surface of traditional magnesia-carbon brick aggregates consists of exposed, highly reactive pure MgO crystals, which are extremely soluble in acidic slag. Existing technologies often improve the material's erosion resistance by introducing Cr2O3 and ZrO2 powders. However, these powders are isolated and dispersed in the matrix, lacking solid solution bonding with the MgO component. Upon contact with acidic slag, the MgO component still undergoes dissolution, rendering the aforementioned erosion-resistant components ineffective. Cr2O3 is an amphoteric, slightly acidic oxide. During high-temperature pre-sintering, Cr... 3+ Ions enter the MgO lattice and replace part of the Mg²⁺. +Ions form a solid solution. This ion substitution significantly reduces the overall alkalinity of the magnesia surface. For acidic slag, the magnesia surface with dissolved Cr2O3 exhibits significantly enhanced inertness to the acidic slag, fundamentally reducing the chemical driving force for the slag to dissolve into the aggregate.
[0011] Lattice distortion and defects "capture" foreign ions: due to Cr 3+ (Trivalent) replaced Mg 2+ (Polyvalent), to maintain the electroneutrality of the crystal, cation vacancies (magnesium vacancies) inevitably arise in the MgO lattice. These surface lattice defects and distortions not only make the crystal surface more compact, but also preferentially allow other ions (such as Fe²⁺) that have penetrated into the slag to be introduced into the slag upon contact with the molten slag. + Ti 4+ The material is "captured" in these vacancies, forming an extremely stable and complex solid solution, thereby "locking" the corrosive material in the surface and preventing it from diffusing into the depths of the aggregate.
[0012] In-situ generation of a dense magnesium chromium spinel isolation layer: By controlling the solid solubility, a chemically inert magnesium chromium spinel (MgCr2O4) shell is pre-constructed on the aggregate surface. When acidic slag comes into contact with the aggregate, it faces a spinel phase with a high melting point and strong resistance to acidic slag dissolution, thus fundamentally cutting off the violent interfacial reaction between alkaline aggregate and acidic slag, protecting the aggregate core from erosion.
[0013] Effects of the Invention Compared with the prior art, the present invention has the following beneficial effects: Excellent resistance to chemical erosion and penetration by acidic slag: By pre-regulating the solid solution and spinelization of Cr2O3 on the surface of magnesia aggregate, the inherent problem of pure periclase aggregate being susceptible to chemical erosion by acidic slag is solved. This significantly delays the wear and tear on furnace lining materials caused by low-basicity acidic slag under conditions such as non-ferrous smelting and special steel refining.
[0014] Excellent high-temperature densification and volume stability: The modified aggregate eliminates abnormal reactive expansion during subsequent brick-making processes, and the material exhibits low porosity, high strength, and erosion resistance. Significant economic and engineering value: The preparation process is simple and stable, precisely confining expensive and environmentally restricted chromium to the aggregate surface, greatly reducing the overall chromium content in the formulation. The resulting magnesia-carbon refractories can significantly extend the service life of related kilns in acidic slag environments, reducing shutdown frequency and maintenance costs. Attached Figure Description
[0015] Figure 1 The images show the microstructure of the solid solubility-controlled modified magnesia aggregate prepared in Example 1 of this invention, and the microstructure of the magnesia-carbon refractory material containing modified MgO-Cr2O3 aggregate after an erosion test. After erosion, the slag is trapped around the modified magnesia aggregate, significantly improving its erosion resistance. Detailed Implementation
[0016] The technical solution and effects of this application are further illustrated by the following embodiments: To avoid repetition, the aggregate and particle size distribution and basic raw material parameters involved in each embodiment are uniformly described as follows: Solid solution modified aggregate distribution: 40 parts for 5-3 mm, 35 parts for 3-1 mm, and 25 parts for 1-0.1 mm. SiC particle distribution: 30 parts for 3-1 mm and 70 parts for 1-0.1 mm. Matrix powder: 74μm (200 mesh) high-purity flake graphite fine powder; α is micro powder; Si powder and B4C powder purity >95wt%.
[0017] Example 1
[0018] (1) Preparation of pre-sintered solution-modified aggregate: Weigh 80 parts of fused magnesia particles with a particle size of 5-0.1 mm and a particle size D 50 Twenty parts of 2μm Cr2O3 micropowder were mixed with a 3% (w / w) polyvinyl alcohol aqueous solution as a temporary binder in a mixer. The mixture was then pressed into cylindrical blocks of Φ50mm × 50mm under 60 MPa pressure. The blocks were placed in a high-temperature electric furnace and pre-sintered at 1600℃ in air for 4 hours for solution treatment. After cooling, the blocks were crushed and graded using a standard sieve, collecting chromium oxide surface-modified magnesia aggregates of 5–3 mm, 3–1 mm, and 1–0.1 mm for later use. Microstructural analysis showed that the aggregate surface was completely coated with a continuous MgCr2O4 spinel layer.
[0019] (2) Weigh the following brick-making raw materials by mass percentage: 52 parts of the above-mentioned chromium oxide solution-modified magnesia aggregate; 18 parts of SiC particles; 7 parts of conventional fused magnesia fine powder (< 0.074 mm); 1.5 parts of SiC fine powder (< 0.044 mm); 2.5 parts of flake graphite fine powder; 1.5 parts of α-Al2O3 micro powder; 1.0 part of high-temperature asphalt powder; 2.5 parts of metallic Si powder; 1.0 part of B4C powder; 3.5 parts of liquid phenolic resin (added).
[0020] (3) Mixing and molding: The weighed solution-modified magnesia aggregate and SiC particles were premixed in a high-strength mixer for 3 minutes; then liquid phenolic resin was added and mixed for another 5 minutes to uniformly wet the spinel layer on the surface of the modified aggregate; the remaining conventional magnesia fine powder, SiC fine powder, flake graphite fine powder, α-Al2O3 micro powder, asphalt powder, Si powder and B4C powder were premixed evenly and then poured into the mixture, and the mixture was stirred and kneaded for another 12 minutes. The resulting uniform material was pressed into standard bricks at a pressure of 120 MPa on a brick press, and then placed in a drying oven and kept at 200℃ for 24 hours to obtain the modified acid-resistant slag magnesia-carbon refractory material sample.
[0021] (4) Performance testing: The refractory material prepared in this embodiment, after drying at 200℃, has a bulk density of 3.18 g / cm³. 3 The apparent porosity was 6.2%, and the compressive strength at room temperature was 64 MPa. The sample was processed into a standard crucible and filled with typical industrial high-silica slag (chemical composition: SiO2 45wt%, FeO 25wt%, CaO 8wt%, Al2O3 10wt%, MgO 5wt%, other 7wt%). It was held at 1600℃ in air for 0.5 hours. After cooling, it was cut open for observation: the slag penetration depth was extremely slight (<0.8mm); scanning electron microscopy revealed that due to the chemical passivation effect of the surface magnesium chromium spinel layer, the periclase core of the modified aggregate did not undergo any outward dissolution or erosion, and the erosion interface was extremely smooth and clear. Simultaneously, in an air oxidation resistance test held at 1000℃ for 3 hours, its mass loss was only 1.6%.
[0022] Example 2
[0023] (1) Preparation of pre-sintered solution-modified aggregate: 75 parts of 5-0.1 mm reburned magnesia particles and 25 parts of Cr2O3 micro powder were weighed. A 3.5% sodium carboxymethyl cellulose aqueous solution was added and mixed well, and the mixture was pressed into spheres under a pressure of 70 MPa. The spheres were kept at 1620℃ in air for 3.5 hours. After cooling, crushing, and sieving, chromium oxide solution-modified magnesia aggregates of various grades were collected.
[0024] (2) Weigh the following brick-making raw materials by mass percentage: 56 parts of the above-mentioned chromium oxide solution modified magnesia aggregate; 14 parts of SiC particles; 6 parts of unmodified pure magnesia fine powder; 2.0 parts of SiC fine powder; 2.5 parts of flake graphite fine powder; 1.5 parts of α-Al2O3 micro powder; 1.0 parts of high-temperature asphalt powder; 3.0 parts of metallic Si powder; 1.0 parts of B4C powder; 3.5 parts of liquid phenolic resin (added).
[0025] (3) Mixing, molding and heat treatment: The process steps are the same as in Example 1. The mixture is pressed into shape at 130 MPa and dried at 210°C for 24 hours.
[0026] (4) Performance testing: The bulk density of the refractory material prepared in this embodiment is 3.22 g / cm³. 3 The apparent porosity is 5.9%, and the compressive strength at room temperature is 68 MPa. After a 0.5-hour erosion test by low-calcium acidic slag from copper smelting high-speed iron at 1600℃, the cross-section showed no erosion or deterioration of the aggregate, indicating that the magnesium-chromium solid solution protective layer on its surface resisted the high-temperature erosion of the acidic polymetallic slag. In an oxidation resistance test at 1000℃, the mass loss was only 1.4%.
[0027] Example 3
[0028] (1) Preparation of pre-sintered solution-modified aggregate: Weigh 85 parts of high-quality fused magnesia particles (5-0.1 mm) and 15 parts of Cr2O3 micro powder. Add 3% by mass of temporary binder and mix well. Press into briquettes at 55 MPa. Keep warm at 1580℃ in air atmosphere for 5 hours. After cooling, crushing, and sieving, collect chromium oxide surface solution-modified magnesia aggregates of various grades.
[0029] (2) Weigh the following brick-making raw materials by mass percentage: 60 parts of the above-mentioned chromium oxide solution-modified magnesia aggregate; 10 parts of SiC particles; 8 parts of conventional pure magnesia fine powder; 2.0 parts of SiC fine powder; 2.0 parts of flake graphite fine powder; 1.5 parts of α-Al2O3 micro powder; 1.0 part of high-temperature asphalt powder; 3.5 parts of metallic Si powder; 1.0 part of B4C powder; 3.5 parts of liquid phenolic resin (added).
[0030] (3) Mixing, molding and heat treatment: The process steps are the same as in Example 1. The molding pressure is 140 MPa and the drying conditions are 190℃ for 24 hours.
[0031] (4) Performance Testing: The refractory material prepared in this embodiment has a bulk density of 3.12 g / cm³, an apparent porosity of 6.5%, and a room temperature compressive strength of 61 MPa. After the same erosion test at 1600℃ with high silica slag (basicity 0.5), the modified periclase aggregate exhibited high chemical stability, effectively resisting the physical penetration and chemical erosion of the strong acid slag. In the oxidation resistance test at 1000℃, the mass loss was 1.9%.
Claims
1. A method for preparing a magnesia-carbon refractory material resistant to acid slag erosion, characterized in that, Includes the following steps: (1) Preparation of chromium oxide solution modified magnesia aggregate: By mass fraction, 70-85 parts of magnesia particles of 5-0.1 mm and 15-30 parts of Cr2O3 micro powder are mixed and a temporary binder is introduced. After molding, the mixture is pre-sintered at a high temperature of 1550℃-1650℃ for 3-5 hours to allow chromium oxide and periclase to react and dissolve on the surface of the particles and form a magnesia-chromium spinel layer. After cooling, crushing and grading, the chromium oxide solution modified magnesia aggregate of each particle size is collected. (2) Ingredients: The raw material composition and mass ratio of the refractory material are as follows: 50-62 parts of chromium oxide solution modified magnesia aggregate, 10-20 parts of SiC particles, 5-10 parts of pure magnesia fine powder, 1-3 parts of SiC fine powder, 2-4 parts of flake graphite fine powder, 1-3 parts of α-Al2O3 micro powder, 0.5-1.5 parts of pitch powder, 2-4 parts of metallic Si powder, 1-1.5 parts of B4C powder, and 3-4 parts of added liquid phenolic resin; (3) Mixing and molding: First, mix the solution-modified magnesium sand aggregate and SiC particles, then add phenolic resin to wet the surface of the aggregate, and finally add the matrix mixture powder premixed with the remaining powders. After mixing evenly, press the mixture under a pressure of 100-150 MPa. (4) Heat treatment: The molded body is dried at 180℃~220℃ for 24 hours to obtain a magnesium-carbon refractory material with enhanced resistance to acid slag erosion.
2. The method for preparing chromium oxide solution-modified magnesia aggregate reinforced with acid slag erosion-resistant magnesia-carbon refractory material according to claim 1, characterized in that: The average particle size D of the Cr2O3 micro powder mentioned in step (1) 50 The particle size is 1-5 μm and its purity is >99.0 wt%; the temporary binder is an aqueous solution of polyvinyl alcohol or an aqueous solution of sodium carboxymethyl cellulose, and the amount of temporary binder added is 2-4% of the total amount of magnesium sand particles and Cr2O3 micro powder.
3. The method for preparing magnesia-carbon refractory material resistant to acid slag erosion according to claim 1, characterized in that: In step (2), the chromium oxide solution-modified magnesia aggregate contains 35-45 parts of 5-3 mm aggregate, 30-35 parts of 3-1 mm aggregate, and 20-30 parts of 1-0.1 mm aggregate; and in the SiC particles, 20-40 parts of 3-1 mm SiC particles and 60-80 parts of 1-0.1 mm SiC particles.
4. The method for preparing magnesia-carbon refractory material resistant to acid slag erosion according to claim 1, characterized in that: In step (3), the modified aggregate and SiC particles are premixed in a mixer for 3 to 5 minutes, phenolic resin is added and the mixture is continued for 4 to 7 minutes, and finally the matrix mixing powder is added and the mixture is continued for 10 to 15 minutes until the material is uniform.
5. The method for preparing magnesia-carbon refractory material resistant to acid slag erosion according to claim 1, characterized in that: The obtained refractory material, after heat treatment at 200℃ for 24 hours, has a bulk density of 3.05–3.35 g / cm³. 3 The apparent porosity is 5.5%–7.5%, and the compressive strength at room temperature is 58–72 MPa. Under high-temperature acidic slag erosion conditions, the magnesia-chromium spinel layer on the surface of the modified magnesia aggregate has a chemical passivation effect, which can prevent the slag from chemically dissolving and chemically penetrating the magnesia aggregate.